Effects of chitosan with vegetable oil on shelf life of brown trout (Salmo trutta fario) fillets fed on prebiotics. Issue 5 (16th July 2019) - Yumuk, Hurrem; Alak, Gonca; Yanik, Telat
Abstract: In this research, effects of chitosan coating of brown trout ( Salmo trutta fario ) fillets containing inulin were determined. Chitosan enriched by vegetable oils (0% Chitosan‐control, 2% acetic acid +Chitosan, 2% sage oil+Chitosan, and 2% mint oil+Chitosan) on shelf life was investigated. In the experiment, fish fillets from the control and the experimental groups were subjected to chemical and microbiological analyses at 0, 3, 6, 9, and 12 days of cold storage at 4 ± 1°C. Coating with chitosan enriched with different vegetable oils caused statistically significant effects on microbiological (total aerobic mesophilic, psychrotrophic, lactic acid, Enterobacteriaceae, and Pseudomonas ) and chemical parameters (total volatile base–nitrogen and pH) ( p < .05), but not on thiobarbituric acid reactive substance values ( p > .05). Considering all of the data determined from the present study, it was found that fish fillets coated with chitosan enriched with mint oil gave the best results with respect to shelf life. Practical Application: To use chitosan as coating material in fish processing. To enrich chitosan with vegetable oils for longer shelf life of fillets of brown trout fed on prebiotic, inulin. To report use of mint oil with chitosan as coating substance for the best results in storage of aquatic products.